Predictors, clinical impact, and management strategies for conduction abnormalities after transcatheter aortic valve replacement: an updated review - Yu, Qingyun; Fu, Qingan; Xia, Yunlei; Wu, Yanqing (Frontiers in Cardiovascular Medicine, 2024)
Transcatheter aortic valve replacement (TAVR) has increasingly become a safe, feasible, and widely accepted alternative surgical treatment for patients with severe symptomatic aortic stenosis. However, the incidence of conduction abnormalities associated with TAVR, including left bundle branch block (LBBB) and high-degree atrioventricular block (HAVB), remains high and is often correlated with risk factors such as the severity of valvular calcification, preexisting conditions in patients, and procedural factors. The existing research results on the impact of post-TAVR conduction abnormalities and permanent pacemaker (PPM) requirements on prognosis, including all-cause mortality and rehospitalization, remain contradictory, with varied management strategies for post-TAVR conduction system diseases across different institutions. This review integrates the latest research in the field, offering a comprehensive discussion of the mechanisms, risk factors, consequences, and management of post-TAVR conduction abnormalities. This study provides insights into optimizing patient prognosis and explores the potential of novel strategies, such as conduction system pacing, to minimize the risk of adverse clinical outcomes.